Diclofenac Sodium and Hippocampus: a Brief Evaluation - Gasmalla, H.E.E.; Tufekci, K.K.; Nurein, M.A.; Kaplan, S. (Nova Science Publishers, Inc., 2021)
The purpose of this chapter is to highlight the relationship between oxidative stress (OS) as a mechanism by which diclofenac sodium (DS) can affect the hippocampus, the vulnerability of the hippocampus to OS, and the responsiveness of both DS and hippocampus to antioxidants. This review also explores other studies that evaluate the effect of DS on the hippocampus. The hippocampus is a part of the hippocampal formation (HF) that is involved in functions related to memory, learning, and emotions. DS as one of the non-steroidal anti-inflammatory drugs (NSAIDs) is a phenylacetic acid derivative, it is known as an anti-inflammatory, analgesic, and antipyretic drug. Studies suggest that the toxicity of DS is induced by OS and reduced by antioxidants; the hippocampus is a vulnerable region and affected by OS. It is also responsive to the protective roles of substances having antioxidant activities, considering this; many antioxidants have been proven to be neuroprotective. Several studies used antioxidants to minimize the effect of OS on the nervous tissues. It indicates the useful effect of antioxidants, on the other hand, randomized controlled trials have concluded that antioxidants have no significant effects on Parkinson disease (PD) and Alzheimer disease (AD), both diseases associated with OS. The probable explanation for unexpected result might be due to limitations regarding the generalization of the results obtained from animals on humans. It is a general rule that animal models cannot mimic the same long duration of disease development or ageing processes. Other factors include dosage differences between animal models and humans, and using an antioxidant that scavenges reactive oxygen species (ROS) rather than eliminating the source of their production is also a contributing factor. There are different mechanisms of OS with different sources of ROS, thus the use of multiple antioxidants would be more beneficial, also, it looks crucial to administer antioxidants in early stages or prior to disease development, more work in this field is needed. © 2021 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Antioxidants; Diclofenac Sodium; Hippocampus; NSAIDs; Oxidative Stress